2003
DOI: 10.1007/s00284-002-3951-y
|View full text |Cite
|
Sign up to set email alerts
|

2-Ketogluconic Acid Production and Phosphate Solubilization by Enterobacter intermedium

Abstract: Enterobacter intermedium, isolated from grass rhizosphere, exhibited a strong ability to solubilize insoluble phosphate. This bacterium oxidized glucose to gluconic acid and sequentially to 2-ketogluconic acid (2-KGA), which was identified using HPLC and GC-MS. The ability of E. intermedium to solubilize phosphate and produce 2-KGA produce in broth medium containing different components was monitored with air and without air supply. With an air supply, the production of 2-KGA markedly increased to about 110 g/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(24 citation statements)
references
References 19 publications
3
20
0
1
Order By: Relevance
“…A strong negative correlation (r=-0.89; p<0.01) between the content of soluble phosphorus and pH was observed. It was accordance with some studies which also showed a negative correlation between soluble phosphorus released and pH in phosphate solubilization [21,22].…”
Section: Characteristics Of Rp Solubilization By the Isolatessupporting
confidence: 92%
“…A strong negative correlation (r=-0.89; p<0.01) between the content of soluble phosphorus and pH was observed. It was accordance with some studies which also showed a negative correlation between soluble phosphorus released and pH in phosphate solubilization [21,22].…”
Section: Characteristics Of Rp Solubilization By the Isolatessupporting
confidence: 92%
“…Bacterial mineral phosphate solubilization has been attributed to the activity of glucose dehydrogenase; a membrane bound enzyme that is involved in the direct oxidation of glucose to gluconic acid, which subsequently gets converted to 2-ketogluconic acid and 2, 5-diketogluconic acid (Goldstein 1995). The 2-ketogluconic acid is more effective than gluconic acid in solubilizing phosphate (Kim et al 2002). In a dramatic shift from the past, there has been a surge of interest on P solubilization at cold temperatures by natural and mutant psychrotolerant strains in the present decade (Katiyar and Goel 2003;Trivedi and Sa 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently gluconic acid is enzymatically converted to 2-ketogluconic acid and 2,5-diketogluconic acid. The 2-ketogluconic acid is more effective than gluconic acid in solubilizing phosphate (Kim et al 2002). While most earlier studies on this phenomena were restricted to mesophilic temperatures (Chung et al 2005;Chen et al 2006), recent studies have shifted the focus to P solubilization by mutant strains at the psychrotolerant range (Katiyar & Goel 2003; a Values are the mean of ten replicates.…”
Section: Discussionmentioning
confidence: 99%